TI_GERICHTE 80.2020.163 vom 30. Juli 2020 , Procedura: ricorso, spese, ripetibili a avvocato rappresentato da un collega - TI Tribunale d'appello (2020)
Procedura: ricorso, spese, ripetibili a avvocato rappresentato da un collega